Kommentarer til Sven Tarp: Retskrivningsordbog på godt og ondt - Andersen, Margrethe Heidemann; Jensen, Jørgen Nørby; Jervelund, Anita Ågerup (LexicoNordica, 2016)
This article is a comment on some of the criticisms which Sven Tarp puts forward in his article Retskrivningsordbog på godt og ondt in LexicoNordica 20. Sven Tarp’s criticism has been accepted on a num‑ ber of points, for example, that it would have been more practical if a user of the digital version of Retskrivningsordbogen (the official dictionary of Danish Orthography) could be redirected from the archaic spelling to the new and correct spelling. With regard to other criticisms, however, we are somewhat more hesitant. Thus, we are looking for clear guidelines on how “the lexicographical principles on proscription” are to be realized efficiently in dictionaries.